Blagovna znamka Ljubljanske banke - Rendla, Marta (Prispevki za novejšo zgodovino, 2022)
In the following paper, the author makes use of the archival materials about the Ljubljanska bankabank, its eponymous internal newsletter, and the relevant literature to present the development of this leading Slovenian bank’s trademark during the socialist period. Ljubljanska banka was the first bank in the Yugoslav territory to recognise branding as an essential marketing instrument and a part of its marketing and communication strategy in the early 1970s. To this end, it developed a uniform public image or a corporate identity – a distinctive logo used in all communication media, and a corporate identity of its buildings – a house style. The bank recognised the trademark, which was also developed through the general public perceptions of the banking services it provided, as the primary means of building its reputation, establishing itself in the market, and maintaining its identity and integrity. Ljubljanska banka started using the trademark to present itself and, after the transformation and reorganisation in 1978, the entire system of its banks. In practice, the bank’s corporate design established itself as a vital element of the identity of the whole Ljubljanska bankasystem
Keywords: bančništvo; blagovna znamka; Jugoslavija; logo; marketing; socializem; vizualne komunikacije